2018
DOI: 10.16966/2380-5536.150
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of a National School-based HIV Prevention Intervention for Primary School Children in Kenya

Abstract: Primary schools in Kenya provide a promising venue for widespread delivery of HIV prevention interventions. This article describes the development and evaluation of Making Life’s Responsible Choices (MLRC), a school-based HIV prevention intervention for primary school children developed through a collaborative global partnership involving multiple community stakeholders. Intervention development was informed by extensive reviews of youth-focused evidence-based HIV prevention interventions, and was rooted in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Consistent with other studies (Harper et al, 2018;Peskin et al, 2015), this SRH educational intervention demonstrated positive effects on middle school students' SRH-related knowledge that emerged immediately after the intervention, which persisted 1 month later. The effectiveness of SRH-related knowledge among adolescents might be influenced by two conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with other studies (Harper et al, 2018;Peskin et al, 2015), this SRH educational intervention demonstrated positive effects on middle school students' SRH-related knowledge that emerged immediately after the intervention, which persisted 1 month later. The effectiveness of SRH-related knowledge among adolescents might be influenced by two conditions.…”
Section: Discussionsupporting
confidence: 86%
“…PLHIV's concerns about health protection in conjunction with the importance of health‐promoting behaviours, and the adverse effects of HIV on society highlight regularly obtaining PLHIV's perspectives about health‐promoting behaviours and understanding their level of awareness. Many HIV‐related studies have focused on the development and evaluation of short‐term nursing interventions, using quantitative approaches (Harper et al, 2018; Khani et al, 2020; Ravalihasy et al, 2022). However, qualitative research, as an exploratory approach, lays the ground for conducting more in‐depth studies on various aspects of the topic.…”
Section: Introductionmentioning
confidence: 99%